Pulsemeeter - A virtual mixer for linux - Carneiro, Gabriel Rodrigues Chaves; Schiavoni, Flávio Luiz (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2025: Anais Estendidos do XIX Simpósio Brasileiro de Computação Musical, 2025)
Pulsemeeter is an application designed to simplify audio management in computer systems. Much like certain mixers group audio sources, the computer’s audio system comprises categories such as games, music players, system sounds, and video players, which can be grouped and have their volumes regulated to control the system’s sound output. Given that users might engage with multiple applications within these categories simultaneously, this work proposes an abstraction layer that groups similar applications. It aims to offer a more generalized manipulation of system sound sources without requiring constant micromanagement when adjustments are needed. This application aims to streamline the process while retaining the flexibility for specific adjustments if required. Notably, it seeks to provide a viable alternative to virtual mixers like Voicemeeter, specifically tailored for Linux systems. The application’s focus lies in simplifying audio control without compromising on versatility, targeting improved user experience within the Linux environment.